A tanyai iskolarendszer változása a Hódmezővásárhely környéki településszerkezet megváltozásának hatására - Gálné Horváth, Ildikó (Közép-Európai Közlemények, 2009)
In town Hódmezővásárhely schools out of the town have had big role since 1930, which could be found in 5 km radius around border of the town. Changing of farm schools is a good mirror of structural forming of population. Single districts became depopulated during the history, the schools closed down gradually there. People were moving into towns during last 40 years, so population in boondocks decreased. In 1995/1996 academic year only 5 worked, they closed down 2 years ago. These schools made force – from the beginning during one and half century – for development of boondocks schools and next generation tells thanks for more generations farm schooling. The farm schools completed their historical mission. It the last ones also lost their pupils, farm centers it was necessary to face up to challenges.